2022
DOI: 10.3390/s22218529
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Gas Sensors with Polycomposite Coatings in Biomedical Application

Abstract: When developing methods for diagnosing pathologies and diseases in humans and animals using electronic noses, one of the important trends is the miniaturization of devices, while maintaining significant information for diagnostic purposes. A combination of several sorbents that have unique sorption features of volatile organic compounds (VOCs) on one transducer is a possible option for the miniaturization of sensors for gas analysis. This paper considers the principles of creating polycomposite coatings on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…• Types: Divided into Bulk Acoustic Wave (BAW) or Quartz Crystal Microbalance (QCM) and Surface Acoustic Wave (SAW) detectors [75][76][77][78][79][80][81].…”
Section: Mass-based Sensorsmentioning
confidence: 99%
“…• Types: Divided into Bulk Acoustic Wave (BAW) or Quartz Crystal Microbalance (QCM) and Surface Acoustic Wave (SAW) detectors [75][76][77][78][79][80][81].…”
Section: Mass-based Sensorsmentioning
confidence: 99%
“…and 10 mg of a DES was incorporated until a transparent solution was obtained. This solution was then applied to the electrode of a piezoelectric quartz resonator (16 MHz, Meteor Plant JSC, Volzhsky, Russia) via dispersion spraying [12]. Subsequently, the coating was placed in an oven at 50 • C for 20 min to remove any unbound ethanol.…”
Section: Formation and Analysis Of Sensitive Layers Of Sensors Based ...mentioning
confidence: 99%
“…The continuous pursuit and synthesis of novel materials to produce sensitive sensor coatings is ongoing [1,2]. Polymer sorbents [3,4], metal-organic structures [5], metal oxides and salts [6,7], carbon nanomaterials [8,9], composite materials [10], and various combinations of the studied sorbents [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Shuba et al [ 4 ] analyzed exhaled breath condensate (EBC) samples obtained from calves to assess the presence of bovine respiratory disease (BRD) using an experimental eight-sensor piezoelectric quartz microbalance (PEQM)-type e-nose. Veterinarians took EBC samples from calves using a special device for collecting exhaled breath into sterile test tubes and froze them in liquid nitrogen for delivery to the laboratory.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%
“…Some of the key findings from the Shuba et al [ 4 ] study indicated that comparative analysis could be used on sets of sensors in the sensor array with different experimental polycomposite coating combinations to improve the efficiency and kinetics of VOC vapor sorption by sensors and to develop relevant polycomposite coatings for detecting specific types of VOCs (targeted for detection) in association with a particular disease. Regression equations were developed to predict the molar-specific sensitivity of the microbalance of VOC vapors using a sensor with a polycomposite coating composed of three distinct sorbent types.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%